Geriatric nutritional risk index predicts poor outcomes in patients with acute ischemic stroke - Automated undernutrition screen tool - Kang, Min Kyoung; Kim, Tae Jung; Kim, Yerim; Nam, Ki-Woong; Jeong, Han-Yeong; Kim, Sung Kyung; Lee, Ji Sung; Ko, Sang-Bae; Yoon, Byung-Woo (PLOS ONE, 2020)
Background Premorbid undernutrition has been proven to have an adverse effect on the prognosis of stroke patients. The evaluation of nutritional status is important, but there is no universally accepted screen methodology. Purpose We aimed to use the geriatric nutritional risk index (GNRI) for evaluating the effect of premorbid undernutrition on short-term outcomes in patients with acute ischemic stroke. Methods A total of 1,906 patients were included for analysis. Baseline characteristics were collected. We evaluated the nutritional status of the patients using the GNRI and body mass index(BMI). The GNRI was calculated as 1.519×serum albumin(g/dL) + 41.7×present weight (kg)/ideal body weight (kg). All patients were categorized into four groups on the basis of the GNRI score. Results Among the included patients, 546 patients had an unfavorable outcomes. The proportion of patients with moderate and severe risk, assessed in GNRI, was significantly higher in the unfavorable outcome group compared to the favorable outcome group (33.3% vs 15.0%). The increased risk of premorbid undernutrition was associated with an increased risk of unfavorable outcome in a dose-response manner after adjusting for covariates. Conclusions This study demonstrated that GNRI was associated with poor prognosis in patients with acute ischemic stroke. GNRI may be used to screen patients at high risk for unfavorable outcome.